Urinary lithiasis and idiopathic hypercalciuria: the importance of dietary intake evaluation - Patricia C. G. Damasio; Carmen R. P. Amaro; Silvia J. P. Berto; Natalia B. Cunha; Ana C. Pichutte; Carlos R. Padovani; Joao L. Amaro (International Brazilian Journal of Urology, 2010)
PUSPOSE: To evaluate food intake of patients with urinary lithiasis and idiopathic hypercalciuria (IH). MATERIALS AND METHODS: Between August 2007 and June 2008, 105 patients with lithiasis were distributed into 2 groups: Group 1 (n = 55) - patients with IH (urinary calcium excretion > 250 mg in women and 300 mg in men with normal serum calcium); Group 2 (n = 50) - normocalciuria (NC) patients . Inclusion criteria were: age over 18, normal renal function (creatinine clearance = 60 mL/min), absent proteinuria and negative urinary culture. Pregnant women, patients with some intestinal pathology, chronic diarrhea or using corticoids were excluded. The protocol of metabolic investigation was based on non-consecutive collection of two 24-hour samples for dosages of: calcium, sodium, uric acid, citrate, oxalate, magnesium and urinary volume. Food intake was evaluated through the quantitative method of Dietary Register of three days. RESULTS: Urinary excretion of calcium (433.33 ± 141.92 vs. 188.93 ± 53.09), sodium (280.08 ± 100.94 vs. 200.44.93 ± 65.81), uric acid (880.63 ± 281.50 vs. 646.74 ± 182.76) and magnesium (88.78 ± 37.53 vs. 64.34 ± 31.84) was significantly higher in the IH group in comparison to the NC group (p < 0.05). As regards the nutritional composition of food intake of IH and NC groups, there was no statistical significant difference in any nutrient evaluated. CONCLUSION: In our study, no difference was observed in the food intake of patients with urinary lithiasis and IH or NC.